Heat pump operated humidification-dehumidification desalination system with option of energy recovery. Issue 18 (11th December 2020) - Lawal, Dahiru U.; Antar, Mohamed A.; Khalifa, Atia; Zubair, Syed M.
ABSTRACT: This study investigates the performance of a novel humidification dehumidification (HDH) desalination system integrated into a vapor compression (VC) heat pump. The integrated heat pump delivers the necessary heating and cooling loads to the HDH desalination unit. Three different layouts (system A, system B, and system C) of water desalination plants are proposed and evaluated analytically at different operating conditions, such as water temperature, water flowrate, mass flowrate ratio (MR), and humidifier effectiveness. The investigated performance metrics of the proposed HDH desalination system are the gained output ratio (GOR), freshwater production rate, specific electrical energy consumption (SEEC), recovery ratio (RR) and cost of freshwater production. System A is without heat recovery, system B has heat recovery through preheating feed inlet saline water, while system C has heat recovery through preheating inlet air to the humidifier. The parametric analysis indicates that GOR, water productivity, and RR improve with increasing water temperature and humidifier effectiveness, while the specific electrical energy consumption decreases at the same conditions. The findings show the existence of an optimum mass flowrate ratio (MR) at which system performances are maximized. Results also reveal that the systems with the option of energy recovery provide the highest gained output ratio, recovery ratio and productivity, and the least specific electrical energy consumption. Additionally, depending on various system and cost parameters, the price of freshwater production from the proposed systems varies from 34.27 $/m 3 to as low as 7.33 $/m 3 of freshwater.